Microstructure evolution and properties of 7075 aluminum alloy recycled from scrap aircraft aluminum alloys - Rui Lin; Bo Liu; Junjie Zhang; Shengen Zhang (Journal of Materials Research and Technology, 2022)
A large quantity of scrap aircraft aluminum alloys in retired aircraft was used to produce cast aluminum alloys as raw material, resulting in a decrease of the value. In this work, the mixture of scrap aircraft aluminum alloys has been grade-maintaining recycled into 7075 aluminum alloy to maximize its recovery value. After melting, composition adjusting, refining and casting, the composition of recycled AA7075 ingots meet the requirements of GB/T 3190-2008, and the final melt is of great cleanliness. Four kinds of recycled AA7075 profiles were prepared by extrusion and T6/T73 heat treatment. The mechanical properties of all recycled profiles are superior to ASTM B209-14 and B221M-13 requirements. The T6-treated bars have the highest tensile strength (591 MPa), yield strength (534 MPa), elongation (10.0%), and stress-corrosion susceptibility factor (44.8). Nevertheless, the stress corrosion cracking, exfoliation corrosion and inter-granular corrosion resistance of the T6-treated bars still meet the requirements of aviation aluminum alloys. Scrap aircraft aluminum alloys can be regarded as master alloys for containing Zn, Mg, Cu, etc., and they have low melting point, fast melting speed, and uniform microstructure. Thus, high-quality 7075 aluminum alloys can be obtained by recycling the scrap aircraft aluminum alloys. Furthermore, the recycling process can provide some guidance for the industrial application of recycling scrap aircraft aluminum alloys.